Adsorption inhibitive properties of Rosmarinus officinalis L. on aluminium AA8011 alloy in 1.0M HCl - Paul A. Andoor; Kelechukwu B. Okeoma; Uchenna S. Mbamara (Zaštita Materijala)
The adsorption mechanism of Rosmarinus officinalis L. as corrosion inhibitor for Al AA8801 alloy in 1.0M HCl was studied using gravimetric method and thermodynamics studies at 303, 313, 323 and 333K. Inhibitor concentrations ranged between 0 and 1000mg/L. Results show that the adsorption mechanism of Rosmarinus officinalis L. is via physisorption, generally endothermic and accompanied by a resulting decrease in disorder. Inhibitor efficiency largely decreased with increase in temperature, and decrease in concentration of the extract. The presence of an external magnetic field enhanced the dissolution of passivating Al2O3 films, thereby increasing corrosion rate.